2017
DOI: 10.1111/jce.13307
|View full text |Cite
|
Sign up to set email alerts
|

Predicting appropriate shocks in patients with heart failure: Patient level meta‐analysis from SCD‐HeFT and MADIT II

Abstract: Background No precise tools exist to predict appropriate shocks in patients with a primary prevention ICD. We sought to identify characteristics predictive of appropriate shocks in patients with a primary prevention implantable cardioverter defibrillator (ICD). Methods Using patient-level data from the Multicenter Automatic Defibrillator Implantation Trial II (MADIT II) and the Sudden Cardiac Death in Heart Failure Trial (SCD-HeFT), we identified patients with any appropriate shock. Clinical and demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
1
15
1
1
Order By: Relevance
“…Accordingly, in this study almost half of the patients with LVEF < 35% showed no recurrence of ventricular tachyarrhythmias at 5 years. A meta-analysis of the SCD-HeFT and MADIT-II trials revealed that 80% of patients with LVEF < 35% and primary preventive ICD did not experience any appropriate ICD shock at 2.5 years [22]. A prospective observational trial including patients with primary and secondary preventive ICD revealed that LVEF was a poor predictor of appropriate ICD shocks, which is in clear contrast to the results of this study [33].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in this study almost half of the patients with LVEF < 35% showed no recurrence of ventricular tachyarrhythmias at 5 years. A meta-analysis of the SCD-HeFT and MADIT-II trials revealed that 80% of patients with LVEF < 35% and primary preventive ICD did not experience any appropriate ICD shock at 2.5 years [22]. A prospective observational trial including patients with primary and secondary preventive ICD revealed that LVEF was a poor predictor of appropriate ICD shocks, which is in clear contrast to the results of this study [33].…”
Section: Discussioncontrasting
confidence: 99%
“…It was demonstrated that patients with LVEF < 35% benefited from primary preventive ICD implantation with an adjusted relative risk reduction ranging from -23 to -51% [14][15][16][17][18][19][20][21]. A meta-analysis of data from the SCD-HeFT and the MADIT-II trials, which evaluated patients indicated for a primary preventive ICD due to LVEF< 35%, reported that the decrease of LVEF of at least one percentage was associated with an increasing risk of appropriate ICD shocks [22].…”
Section: Introductionmentioning
confidence: 99%
“…Besides increasing the risk of mortality, systolic HF represents one of the most common reasons for increasing the risk of ventricular tachyarrhythmias leading to appropriate device therapies 16,17 . Prescription of MRA was postulated to decrease the risk of ventricular tachyarrhythmias leading to SCD in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the decision to treat patients with MRA may also depend on the severity of HF symptoms [i.e., New York Heart Association (NYHA) class]. A meta‐analysis including data from the MADIT II and SCD‐HeFT trials with more than 1,400 patients with an ICD demonstrated that especially lower LVEF, higher NYHA class, and the absence of beta‐blocker therapy were associated with increased risk of appropriate ICD shockin patients with systolic HF 16 . Thus, MRA may more likely prescribed for patients with higher NYHA class and severe cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several non-invasive risk factors have been studied (Table 4) but few are predictive enough to guide therapy. Comorbidities such as higher NYHA class, lower LVEF, atrial fibrillation and nonsustained VT certainly confer higher risk for arrhythmias (64), yet also increase the proportion of deaths due causes other than to arrhythmias (8) (Figure 3). These and other competing mortality risks limit the effectiveness of ICDs.…”
Section: Understand and Predictmentioning
confidence: 99%